PENGARUH PENAMBAHAN GARAM NaCl PADA LUMPUR PEMBORAN BERBAGAI TEMPERATUR - Widia Yanti; Abdul Hamid; Ibnu Badar Bajri (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2016)
The unidealized of physical and rheological mud can occured when drilling on rock layers with high salt concentrations. It is therefore necessary to add an additive to balance the effect of the salt. The aims of this study is to see the effect of salt addition on various temperature drilling mud.This research will use two types of mud with different oil-water ratio. The drilling mud will be divided into four compositions, ie LA, LB, LC, and LD. LA and LC compositions have an oil-water ratio of 80% oil and 20% fresh water. While LB and LD compositions have oil-water ratio of 75% oil and 25% fresh water. Then the study was conducted at various temperatures, ie 80 °F, 130 °F, 180 °F, 230 °F, 280 °F, and 330 °F. After observing of the physical properties and rheology of drilling mud, it was found that the effect of adding salt NaCl can improve the physical and rheological properties of mud such as density, viscosity, gel strengh, mud cake, and solid content. Conversely, the effect of adding NaCl salt may reduce the nature of electrical stability. While the increasing of the temperature can reduce the physical and rheological properties of mud and on the contrary the loss of water and mud cake will increase.